Mitigation Policies for the Paris Agreement : An Assessment for G20 Countries - Parry, Ian (IMF Working Papers; Working Paper, 2018)
Following submission of greenhouse gas (GHG) mitigation commitments or pledges (by 190 countries) for the 2015 Paris Agreement, policymakers are considering specific actions for their implementation. To help guide policy, it is helpful to have a quantitative framework for understanding: i) the main impacts (on GHGs, fiscal balances, the domestic environment, economic welfare, and distributional incidence) of emissions pricing; ii) trade-offs between pricing and other (commonly used) mitigation instruments; and iii) why/to what extent needed policies and their impacts differ across countries. This paper provides an illustrative sense of this information for G20 member countries (which account for about 80 percent of global emissions) under plausible (though inevitably uncertain) projections for future fuel use and price responsiveness. Quantitative results underscore the generally strong case for (comprehensive) pricing over other instruments, its small net costs or often net benefits (when domestic environmental gains are considered), but also the potentially wide dispersion (and hence inefficiency) in emissions prices implied by countries' mitigation commitments.